Bigeminy: A result of digoxin and St John’s wort interaction - Anđelić Slađana (Vojnosanitetski Pregled, 2003)
A case of an by digoxin under unusual circumstances is reported. An 80-year-old man, previously on long-term digoxin treatment, started consuming St John’s wort herbal tea (2 000 ml/daily) because of frequent episodes of depression. After the cessation of consuming herbal tea containing Hypericum perforatum, digoxin poisoning developed in our patient. Electrocardiography revealed nodal bradicardia 36/min and bigeminy. Manifested symptoms were the consequence of interaction between digoxin and Hypericum perforatum which were consumed simultaneously, and the cessation of consuming St John’s wort herbal tea afterwards. Therapy was the same as in the standard digitalis poisoning. Consumers of St John’s wort combined with medical products are advised not to discontinue tea consumption on their own, without consulting their physician.